Enzyme immunoassay for identification of Vibrio vulnificus in seawater, sediment, and oysters. - Tamplin, M L (1991)
Historically, methods used to identify Vibrio vulnificus in environmental samples have been inadequate because isolation and identification procedures are time-consuming and fail to separate V. vulnificus from other bacterial species. We describe an enzyme immunoassay (EIA) and culture techniques which identified V. vulnificus in seawater, sediment, and oysters. The EIA used monoclonal antibody FRBT37 to a species-specific epitope of V. vulnificus. No cross-reactions were observed among 72 non-V. vulnificus strains comprising 34 species and 15 genera. In field trials, the EIA identified correctly 99.7% of 348 biochemically confirmed V. vulnificus isolates. The epitope corresponding to FRBT37 was found in cells lysed by Triton X-100, deionized H2O, and ultrasonication but was not found in culture supernatants, indicating that its location was intracellular. In addition, electron micrographs of V. vulnificus labeled with FRBT37-biotin-avidin-gold showed that epitope FRBT37 reacted with fragments of lysed cells but not whole cells. FRBT37 was expressed when V. vulnificus was cultured in different growth media. The minimum level of detection of the EIA was approximately 2,000 V. vulnificus cells per EIA well. Epitope FRBT37 was labile at 70 degrees C for 30 min. Immunoblot and EIA plate formats reduced assay time and facilitated handling large numbers of test samples.